Developing a patient safety guide for primary care: A co‐design approach involving patients, carers and clinicians. (3rd November 2020) - Morris, Rebecca L.; Ruddock, Angela; Gallacher, Kay; Rolfe, Carly; Giles, Sally; Campbell, Stephen
Abstract: Background: Patients and carers should be actively involved in patient safety and empowered to use person‐centred approaches where they are asked to both identify safety concerns and partner in preventing them. Objectives: The aim of this study was to co‐design a patient safety guide for primary care (PSG‐PC) to support patients and carers to address key patient safety questions and identify key points where they can make their care safer. The objectives were to i) identify when and how patients and carers can be involved in primary care patient safety, and ii) identify the relevant information to include in the PSG‐PC. Design: An experience‐based co‐design approach. Setting and Participants: We conducted three workshops with patients, carers, community pharmacists and general practitioners to develop and refine the PSG‐PC. Results: Participants identified both explicit and implicit issues of primary care patient safety especially relating to technical and relational components of involving patients and carers. The importance of communication, understanding roles and responsibilities, and developing partnerships between patients and health‐care providers were considered essential for actively involving patients in patient safety. Co‐developing the PSG‐PC provided insight to improve care to develop the PSG‐PC. Discussion: The PSG‐PC is the first guide to be developed for primary care, co‐designed with patients, carers, general practitioners and pharmacists. The PSG‐PC will support patients and carers to partner with health‐care professionals to improve patient safety addressing international and national priorities to continuously improve patient safety.